La antropología filosófica y el problema del hombre. Hacia una concepción de lo humano en Centroamérica - Márquez Guevara, Francisco Antonio (2017)
Starting with a brief historical overview of the philosophical anthropology and its view of the human being, we reflect about our own reality and try to elaborate a contextualized proposal at the Central American level. This includes a search of alienated societies that foster and generate distortions in the human being, causing them to deviate into corruption, greed and ambition, driven by consumerism and accumulation of material possessions. This work envisions the possible future outlining some socio-cultural guidelines that can lead the human development to a change that promotes human beings to flourish, where the access to the esthetic order of the world is plausible and where the spiritual growth takes place.